Studi kasus: Menganalisis kesulitan siswa SMP Negeri 1 Sukanagara pada soal statistika ditinjau dari level kemampuan siswa - Pawitra, Kardiansyah Sukma; Fitriani, Nelly; Senjayawati, Eka (IKIP Siliwangi, 2024)
This study aims to be able to analyze the difficulties of Grade VIII students of SMP Negeri in solving statistical questions. The method used is the case study method. The data used are written tests and interviews. The population and sample in this study were 32 students. The instrument of this study used a questionnaire, namely 6 questions related to statistical questions. Data processing is used by means of written tests and pictures of student answers. The research procedure is the stages of planning, operating, data analysis, and concluding a data. The research will be tested with a number of statistical questions at the application and testing stages, then interviews will be given to several students. The results of the analysis show several criteria based on students' ability to solve statistical problems. Students with high abilities have difficulty in determining the final answer. Students with moderate ability levels experience difficulties in calculating an answer. Students with low ability levels have difficulty understanding the questions given and lack understanding of the material.